Pengembangan Buku Ajar Strategi Pembelajaran Berbasis Proyek dalam Bingkai Keterampilan Abad 21 untuk Calon Guru Sekolah Dasar - Fitri Indriani (Syntax Corporation Indonesia, 2024)
This research aims to produce project-based learning strategy textbook products within the framework of 21st century skills. This research is a type of ADDIE model development research with five stages, namely need assessment, Design, Development, Implementation, Evaluation.Data collection techniques using questionnaires. The results showed that the quality of the assessment of media experts, material experts and student responses obtained an overall score of 267.18 with an average number of 89.06. These results show that project-based learning strategy textbooks in the 21st century skills frame obtain